SOCIAL RESPONSIBILITY IN THE PRACTICE OF CORPORATE GOVERNANCE IN THE LEADING RUSSIAN NON-FINANCIAL TNCS - I. L. Shevchenko (Вестник Кемеровского государственного университета, 2014)
The paper analyzes the performance of the transnational activities of the largest Russian non-financial TNCs, discusses the main aspects of corporate governance practices in the area of social responsibility in these companies and identifies the opportunities to improve the practice.